Efeito da hipóxia aguda na Respiração Superficial Aquática (RSA) e na fisiologia da arraia cururu, Potamotrygon wallacei (Carvalho, Rosa e Araújo, 2016) - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
The present study analyzed the physiological responses and the behavior of aquatic surface respiration (ASR) in a species of freshwater stingray, Potamotrygon wallacei, exposed to conditions of normoxia and acute hypoxia. For this, the stingrays were previously acclimatized in the laboratory under normoxic conditions for 15 days for the elaboration of the ASR ethogram and for 30 days for the physiological analyses. During this period, they were fed daily with pieces of fresh fish, live worms and shrimp until satiation. At the end of acclimatization, the stingrays were randomly distributed in individual aquariums and subjected to two different conditions for 16 consecutive hours: i) normoxia, with a sample number of 4 individuals for the elaboration of the ethogram and 8 individuals for the analysis of physiological data. In this condition, the dissolved oxygen (O2) level was maintained at 74% saturation (~6.0 mg/L) throughout the experiment; ii) acute hypoxia (n = 4 for the ethogram and n = 8 for the analysis of physiological data). In this condition, the O2 levels decreased from normoxic values to at least 18% saturation (1.5 mg/L) in the first eight hours (through the injection of gaseous nitrogen), and then maintained for more eight consecutive hours. All experimental tests carried out in both normoxia and acute hypoxia began at 4:00 pm and ended at 8:00 am the next day, totaling 16 hours of duration. To record the ASR in both experimental groups, the stingrays were filmed throughout the entire time with night viewing cameras (infrared) coupled to a Digital Video Recorder recording system. In addition, physiological parameters such as the frequency of spiracular movements (SF), the erythrogram (hematocrit, hemoglobin concentration, number of erythrocytes and hematimetric indices), the concentration of glucose and lactate in the plasma and of ketone bodies (β- hydroxybutyrate) in the blood. To obtain blood samples, the stingrays were anesthetized with eugenol 75 mg/L. Stingrays exposed to acute hypoxia with 30 days of acclimatization did not manifest ARS. It is believed that the long acclimatization time in normoxic conditions, which do not necessarily occur in the natural environment, especially during the night period in which hypoxia situations are commonly observed, may have modified this behavioral response. On the other hand, newly arrived stingrays kept in acclimatization for up to 15 days, performed the ASR. Regarding the physiological parameters, there was an increase in SF in response to the time of exposure to acute hypoxia (from 38 to 89 beats/min), when compared to those maintained in normoxia, which remained stable (between 40 and 60 beats/min) until the end of the experiment. On the other hand, no changes were observed in the erythrogram, as well as in the concentrations of glucose, lactate and ketone bodies in the group of stingrays exposed to acute hypoxia, when compared with those kept in normoxia. Our study demonstrates that P. wallacei adjusts to acute hypoxia with hyperventilation without depressing metabolism, activating the anaerobic pathway, or utilizing energy stores to obtain glucose.
Effect of acute hypoxia on Aquatic Surface Respiration (ASR) and physiology of cururu stingray, Potamotrygon wallacei (Carvalho, Rosa and Araújo, 2016)
Keywords: Elasmobrânquios; Peixes de água doce - Pesquisa; Arraia (Peixe) - Respiração - Pesquisa; CIENCIAS BIOLOGICAS: FISIOLOGIA; Comportamento respiratório; Elasmobrânquios de água doce; Resposta ventilatória; Eritrograma; Metabólitos plasmáticos